Pirólise de bagaço de malte assistida por micro-ondas - Pimenta, Fernanda Silva (2022)
The use of biomass as an energy source has emerged as a promising alternative for reducing fossil fuel consumption. In this sense, several techniques for converting this material can be used, including thermochemical processes aimed at energy production. Among these processes, microwave-assisted pyrolysis stands out when compared to conventional pyrolysis for time savings, high heating efficiency, and greater process control. This technique makes possible the valorization of biomass through its thermal decomposition in an inert atmosphere, producing three products that normally present higher energy density: biochar, bio-oil, and gas. Pyrolytic products can replace fossil fuels after upgrading processes (Catalytic Upgrading) or be used in the chemical industry. In this work, microwave-assisted pyrolysis of malt bagasse was studied to produce liquid, solid and gaseous products, focusing on the analysis of yields and quality of the liquid product. Through a 2^3 Planning, the effect of the variables temperature, reaction time, and granulometric range of the biomass in the studied process was evaluated and it was identified that the temperature, the granulometric range, and the interaction of temperature and reaction time were the variables that significantly interfered in the pyrolytic liquid yield. In a second step, the Response Surface methodology was used to identify the effect of the variables temperature (X1) and percentage by mass of catalyst, in this case, calcium oxide (X2), studied through a Central Composite Planning (CCP). The compounds present in the bio-oil were identified by gas chromatography coupled to mass spectrometry (GC/MS) and the quality of the same was determined based on the amount of hydrocarbons present. Through PCC using the CaO catalyst, it was possible to obtain equations that describe the studied process, as well as the optimization of the yield and quality (hydrocarbon content) of the bio-oil, reaching a maximum net yield of 30.88%, considering a yield good for the technique used, and a hydrocarbon yield equal to 61.58%. In addition, the results of the composition of the liquid product at the optimum point are promising, and it showed the presence of aromatic hydrocarbons of great interest to the chemical industry. The biochar produced at the optimum point was also characterized and presented 23.6% of fixed carbon and 33.98% of volatiles. Through the results mentioned above, it is highlighted that the use of this biomass as a precursor to biofuels and raw material for the chemical industry via microwave-assisted pyrolysis is a promising area with great potential to be explored in future studies.